2015
DOI: 10.1002/jcb.25262
|View full text |Cite
|
Sign up to set email alerts
|

PRDM1, a Tumor‐Suppressor Gene, is Induced by Genkwadaphnin in Human Colon Cancer SW620 Cells

Abstract: Genkwadaphnin (GD-1) is isolated from the flower buds of Daphne genkwa Siebold et Zuccarini (Thymelaeaceae), and it has been used as a traditional Korean and Chinese medicine. In this study, the authors observe that GD-1 inhibits the growth of the colon cancer cell line, SW620, through the up-regulation of p21 expression in a PRDM1-dependent manner. After treatment with GD-1, the transcriptional repressor PRDM1 is prominently induced in SW620 cells. Furthermore, GD-1 induce the phosphorylation of PKD1 and MEK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…These observations led us to consider an alternative explanation for the maintenance of myeloma cells: Rather than an increase in proliferation, expression of the PRDM1β isoform may inhibit apoptosis. However, some contradictory results were obtained in other studies in which PRDM1α altered the proliferation of HCT116 41 and SW620 47 cells but not RKO colon cancer cells 48 , and ectopic expression of PRDM1 in a chicken fibroblast cell line inhibited cell proliferation 49 . Depending on the cellular context, further studies on the mechanisms of action of the PRDM1 isoforms will be important for understanding their roles in the regulation of apoptosis, cell proliferation and the cell cycle.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These observations led us to consider an alternative explanation for the maintenance of myeloma cells: Rather than an increase in proliferation, expression of the PRDM1β isoform may inhibit apoptosis. However, some contradictory results were obtained in other studies in which PRDM1α altered the proliferation of HCT116 41 and SW620 47 cells but not RKO colon cancer cells 48 , and ectopic expression of PRDM1 in a chicken fibroblast cell line inhibited cell proliferation 49 . Depending on the cellular context, further studies on the mechanisms of action of the PRDM1 isoforms will be important for understanding their roles in the regulation of apoptosis, cell proliferation and the cell cycle.…”
Section: Discussionmentioning
confidence: 90%
“…The transcriptional activity of PRDM1 is essential for the differentiation and maintenance of long-lived plasma cells 3,4 , whose downregulation has been associated with several types of cancer. Therefore, PRDM1 is considered a tumour suppressor gene 23,[43][44][45][46][47] . The two major isoforms, PRDM1α and PRDM1β, are expressed in myeloma cells, while only the PRDM1α isoform is expressed in non-tumorigenic plasma cells 11,28 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the silencing of the cofactor PATZ1 of KLF4 inhibits the colon cancer cell proliferation 38 . The cofactors PRDM1, EGR1, and TOPORS were shown to be tumor suppressors in colon cancer, leukemia, and lung cancer, respectively 3941 . In addition, certain cofactors were verified to have prognostic functions in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Two previous studies of the role of PRDM1 in cell proliferation in HCT116 and SW620 colon cancer cells draw different, contradictory conclusions (22,25). PRDM1 loss of function in these studies was based on knockdown technology in which residual PRDM1 expression could still remain if PRDM1 is maintained at a low level in RKO cells (SI Appendix, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that PRDM1 is activated by specific polymorphic variants of p53 in RKO colon cancer cells (24). Also a recent study showed that PRDM1can inhibit SW620 colon cancer cell proliferation by inhibiting c-Myc (25). The mechanisms by which PRDM1 acts on human colon cells is incompletely understood and may lead to insights relevant to colon cancer and normal intestinal stem cell maintenance.…”
mentioning
confidence: 99%